CREATION OF A COMPUTER-BASED ENVIRONMENTAL MONITORING SYSTEM (Ta'limning zamonaviy transformatsiyasi, 2025)
Annotation. Environmental problems have become almost the most pressing today. The dynamic development of natural resources and the accelerated development of production technology led to an increase in human material well-being, but also contributed to the deepening of the ecological collapse. To solve emerging problems, it is necessary to promote the balance of environmental safety and economic efficiency of the entire national economy.